Diet affects inflammatory arthritis: a Mendelian randomization study of 30 dietary patterns causally associated with inflammatory arthritis - Wang, Haiyang; Wu, Qinglin; Qu, Pengda; Wang, Shiqi; Du, Shiyu; Peng, Zhaorong; Tao, Licheng; Wang, Wuxia; Tang, Xiaohu (Frontiers in Nutrition, 2024)
Background: The causal associations between dietary intake and the risk and severity of Inflammatory Arthritis(IA) are currently unknown. Objective: In this study, we aimed to investigate the causal relationship between nine dietary categories (30 types of diet) and IA using Mendelian randomization (MR). Methods: We analyzed data from 30 diets and IA in a genome-wide association study (GWAS). Single nucleotide polymorphisms (SNPs) that could influence the results of MR analyses were screened out through the Mendelian Randomization Pleiotropy RESidual Sum and Outlier (MR-PRESSO) test. SNPs were analyzed through two-sample bidirectional MR using inverse variance weighting, MR-Egger regression, and weighted median method. The multiplicity and heterogeneity of SNPs were assessed using MR-Egger intercept term tests and Cochran's Q tests. FDR correction was used to correct the P-values. Results： IVW results showed that Beef intake [Odds ratio (OR) = 2.862; 95% confidence interval (CI), 1.360-6.021, p=0.006, p_fdr <0.05] was positively associated with rheumatoid arthritis(RA); Dried fruit intake (OR=0.522; 95% CI, 0.349- 0.781, p=0.002, p_fdr<0.05), and Iron intake (OR=0.864; 95%CI, 0.777-0.960,p=0.007, p_fdr<0.05) were negatively associated with RA, all of which were evidence of significance. Fresh fruit intake(OR=2.528. 95% CI, 1.063-6.011, p=0.036, p_fdr>0.05) was positively associated with psoriatic arthritis (PsA); Cheese intake (OR=0.579; 95% CI, 0.367-0.914, p=0.019, p_fdr>0.05) was negatively associated with PsA; both were suggestive evidence. Processed meat intake (OR=0.238; 95% CI, 0.100-0.565, p=0.001, p_fdr<0.05) was negatively associated with reactive arthritis (ReA), a protective factor, and significant evidence. All exposure data passed the heterogeneity check (Cochrane's Q test p>0.05) and no directional pleiotropy was detected. Leave-one-out analyses demonstrated the robustness of the causal relationship in the positive results. Conclusion： Our study presents genetic evidence supporting a causal relationship between diet and an increased risk of IA. It also identifies a causal relationship between various dietary modalities and different types of IA. These findings have significant implications for the prevention and management of IA through dietary modifications.